Public Private Partnership in Ports Model Concession Agreement - Planning Commission (Planning Commission, 2009)
India’s seaports are vital links in the logistics chain supporting the nation’s international trade and their efficiency is thus key to the competitiveness and growth of the economy. There is today a broad consensus that a sustained growth rate of about 9% per annum is necessary for India to make progress in eliminating poverty and achieving a quantum jump in the quality of life of its citizens. The creation of world class infrastructure is key to sustaining such a growth rate. However, the investment required for overcoming the existing deficit in infrastructure quality and quantity is so large that it cannot possibly be met by relying on the public sector alone.
Planning Commission Government of India
Planning Commission Government of India